US DOD: Contracts (M2 Presswire, 2003)
McDonnell Douglas Corp., a wholly owned subsidiary of The Boeing Co., St. Louis, Mo., is being awarded an $8,562,099,934 fixed-price with economic price adjustment contract for the multi-year procurement of F/A-18E/F airframes. This Multi-Year II (MYP II) contract will cover the procurement of 210 F/A-18E/F aircraft over a 5-year period. Work will be performed in St. Louis, Mo. (60 percent), and El Segundo, Calif. (40 percent), and is expected to be completed in October 2011. Contract funds will not expire at the end of the current fiscal year. This contract was not competitively procured. The Naval Air Systems Command, Patuxent River, Md., is the contracting activity (N00019-04-C-0014). Lockheed Martin Systems Integration, Owego, N.Y., is being awarded a $423,413,424 firm-fixed-priced, multi-year contract for the procurement of 172 common cockpit kits for the MH-60R (71) and MH-60S (101) helicopters from fiscal year 2005 through fiscal year 2008. Work will be performed in Owego, N.Y. (58.8 percent); Farmington, N.Y. (12.9 percent); Woodland Hills, Calif. (10.9 percent); Germantown, Md. (7.7 percent); Salt Lake City, Utah (6.8 percent); and Lewisville, Texas (2.9 percent), and is expected to be completed in December 2008. Contract funds will not expire at the end of the current fiscal year. This contract was not competitively procured. The Naval Air Systems Command, Patuxent River, Md., is the contracting activity (N00019-04-C-0028). Lockheed Martin Systems Integration-Owego, Owego, N.Y., is being awarded a not-to-exceed $11,085,201 cost-plus-incentive-fee delivery order against a previously awarded basic ordering agreement (N00019- 03-G-0014) for one avionics maintenance trainer with functionality for both the MH-60S and MH-60R helicopters. Work will be performed in Owego, N.Y., and is expected to be completed in December 2005. Contract funds will not expire at the end of the current fiscal year. The Naval Air Systems Command, Patuxent River, Md., is the contracting activity.